Analysis of carbon emission reduction contribution during usage phase of new energy vehicles based on big data: A case study of Tianjin - Xia Lina; Li Puchao; Ren Huanhuan; Lu Hao; Zhao Zhenjia (E3S Web of Conferences, 2024)
Countries around the world are paying increasing attention to greenhouse gas emissions reduction. Under the guidance of “dual carbon” strategy in China, the development of the new energy vehicle industry as an important means of carbon emission reduction in the transportation sector has become a trend. At the same time, the Tianjin New Energy Vehicle Monitoring Platform has recorded real-time big data on the operation of new energy vehicles since 2017, covering vehicle ownership and mileage data, which can support the calculation of carbon emission reduction contributions during usage stage of new energy vehicles. Based on the big data of the platform, this article calculates the carbon emission reduction contribution of new energy vehicles in Tianjin during usage stage, and analyzes the carbon emission reduction contributions under different technology types, vehicle types, vehicle classes, and usage scenarios. Moreover, an analysis was conducted on the top ten enterprises in Tianjin that contribute to carbon emission reduction. The reasons for the carbon emission reduction contributions of different enterprises are slightly different, mainly due to high ownership or actual driving mileage.